2019
DOI: 10.1016/j.jag.2019.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Supraglacial rivers on the northwest Greenland Ice Sheet, Devon Ice Cap, and Barnes Ice Cap mapped using Sentinel-2 imagery

Abstract: Supraglacial rivers set efficacy and time lags by which surface meltwater is routed to the englacial, subglacial, and proglacial portions of ice masses. However, these hydrologic features remain poorly studied mainly because they are too narrow (typically <30 m) to be reliably delineated in conventional moderate-resolution satellite images (e.g., 30 m Landsat-8 imagery). This study demonstrates the utility of 10 m Sentinel-2 Multi-Spectral Instrument images to map supraglacial rivers on the northwest Greenland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 69 publications
1
29
0
Order By: Relevance
“…In general, large supraglacial river networks have only recently begun attracting scientific attention with most studies focused on the Greenland Ice Sheet (Colgan et al, 2011;Crozier et al, 2018;Gleason et al, 2016;Ignéczi et al, 2018;King et al, 2016;Lampkin & Vanderberg, 2014;Legleiter et al, 2014;Poinar et al, 2015;Smith et al, 2015;Smith et al, 2017;. Yang et al (2019a) mapped small areas of the Devon and Barnes Ice Caps (as well as the northwest Greenland Ice Sheet) using 10 m Sentinel-2 visible/near-infrared satellite images and found that the drainage patterns and densities of supraglacial river networks may differ significantly within and between different ice masses.…”
Section: Introductionmentioning
confidence: 99%
“…In general, large supraglacial river networks have only recently begun attracting scientific attention with most studies focused on the Greenland Ice Sheet (Colgan et al, 2011;Crozier et al, 2018;Gleason et al, 2016;Ignéczi et al, 2018;King et al, 2016;Lampkin & Vanderberg, 2014;Legleiter et al, 2014;Poinar et al, 2015;Smith et al, 2015;Smith et al, 2017;. Yang et al (2019a) mapped small areas of the Devon and Barnes Ice Caps (as well as the northwest Greenland Ice Sheet) using 10 m Sentinel-2 visible/near-infrared satellite images and found that the drainage patterns and densities of supraglacial river networks may differ significantly within and between different ice masses.…”
Section: Introductionmentioning
confidence: 99%
“…Their multispectral visible-wavelength sensors have a fine radiometric resolution (12-bit), similar to Landsat-8, enabling reliable detection of subtle changes in surface reflectance at a 10-m spatial resolution regularly (e.g. Fahnestock and others, 2016; Yang and others, 2019). While multiple other high-sensitivity visible-wavelength multispectral sensors now exist, including Landsat-8 and the WV constellation, we opted to primarily use S2 imagery for the examination of the GrIS surface stratigraphy.…”
Section: Methodsmentioning
confidence: 99%
“…Their multispectral visible-wavelength sensors have a fine radiometric resolution (12-bit), similar to Landsat-8, enabling reliable detection of subtle changes in surface reflectance at a 10-m spatial resolution regularly (e.g. Fahnestock and others, 2016;Yang and others, 2019). While multiple other highsensitivity visible-wavelength multispectral sensors now exist, including Landsat-8 and the WV constellation, we opted to primarily use S2 imagery for the examination of the GrIS surface stratigraphy.…”
Section: Satellite Imagery and Derived Productsmentioning
confidence: 99%